Determinación de Fasciola hepatica y parásitos gastrointestinales en ovinos de la comuna de San Clemente, Chile - Muñoz-Caro, Tamara (2024)
The presence of gastrointestinal parasites (PGI) was determined in meat sheep from farms in the foothills of the commune of San Clemente Chile through convenience sampling (n=100) between August and November 2022. Faecal samples were collected from the rectum. and were processed using the modified Dennis sedimentation technique for the determination of F. hepatica eggs and the Sheather flotation technique for the determination of nematode and coccidia eggs. In addition, the modified McMaster quantitative technique was performed on the samples. A higher prevalence of parasites from the Trichostrongylidae family (68%) was found, followed by F. hepatica (47%), Nematodirus sp (25%) and Eimeria sp (43%). In addition, the epidemiological variables age, sex and health status were evaluated. The age group was significant (p=0.003) for the age variable in Trichostrongylidae, and the type of health management affected the prevalence of Eimeria (p=0.020); Trichostrongylidae (p=0.001); Nematodirus sp (p=0.04) and F. hepatica (p=0.020). Moderate parasite loads were detected in all cases. Likewise, cases of biparasitism (26%) and multi-parasitism (32%) were detected.